Pemberdayaan Masyarakat melalui Edukasi dan Praktik Pembuatan Eco Enzyme: Studi Kasus Desa Karangkandri, Cilacap - Antonius Indra Wicaksono; Hery Widijanto; Putri Nida Fahira; Yusrina Zakiyah; Alifya Rafaninda Ayuningtyas; Ningrum Caesarena Angela Samudra; Salma Fauziah Raudatul Jannah; Nurul Wahidah; Denada Dian Saraswati; Didik Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This activity aims to develop the potential of the community, particularly the PKK women’s group of Karangkandri Village, through education and training in eco-enzyme production. The waste problem arises from household residues that have not undergone further processing. By directly observing the existing issues, this study applies a participatory action research (PAR) approach that combines education and hands-on practice of eco-enzyme making. The activity resulted in eco-enzyme products made by the participants. Moreover, the participants were enthusiastic throughout the program and planned to continue practicing it at home to address problems such as unpleasant odors in animal pens, agricultural applications, and as a cleaning agent, for example dishwashing. The conclusion of this activity is that eco-enzymes have the potential to serve as an environmentally friendly natural cleaner as well as a strategy for household waste management.